A Resource-Based View Approach to Understanding the Dynamics of Competitive Advantage: A Case Study of Ayam Salto Bandar Lampung - Adhe Elasno; Daffa Ilyasa Aras; Palupi Patmasari; Vicky F Sanjaya (Managing: Jurnal Bisnis dan Manajemen, 2026)
The rapid development of fast food in Indonesia has placed MSMEs such as Ayam Salto in increasingly intense competition, making the management of resources that meet VRIN criteria a key factor for sustainable competitive advantage. This study aims to map the main resources and capabilities of Ayam Salto using the Resource-Based View framework and analyze their contribution to the formation of business differentiation. Through a qualitative case study approach involving interviews, observations, and document analysis, the findings show that unique recipes, consistent service patterns, and a brand image based on local identity are core assets that are difficult to imitate and not easily substituted, thereby strengthening the company's competitive position. This study confirms that the strategic utilization of VRIN resources, supported by adaptive and innovative capabilities, is an important foundation for culinary MSMEs to maintain competitiveness in the fast food market.